Effect of 5% Binahong (Anredera cordifolia) Leaf Extract Gel on Macrophage Activity in Wound Healing After Tooth Extraction in Wistar Rats - Romadhona, Naila Fadhilah; Suparno, Nilasary Rochmanita; Murika Sari, Nendika Dyah Ayu; Ningsih, Juwita Raditya (Sarana Ilmu Indonesia (salnesia), 2024)
Tooth extraction is an action that is often performed in the world of dentistry to remove intact teeth or remaining roots from the sockets in the alveolar bone. Macrophage cells are important processes in wound healing during the inflammatory phase. Binahong leaves (Anredera cordifolia) contain flavonoids, ascorbic acid, tannins, terpenoids, saponins, alkaloids which influence macrophage activity. The aim of the research was to determine the effect of 5% binahong (Anredera cordifolia) leaf extract gel on the increase in macrophages after tooth extraction in Wistar strain white rats. This type of research was pure experimental research with a post test only group design. The research subjects were 36 mice divided into negative control, positive control and treatment groups. The left mandibular incisor was removed and CMC-NA 1%, glycerin iodine 1%, and 5% binahong (Anredera cordifolia) leaf extract gel were applied. The lower incisors of mice were extracted and then made histological preparations stained with hematoxylin then divided into 3 groups, then the number of macrophages was counted using a microscope with 400x magnification. The One Way Anova parametric test showed that there was a significant difference (p<0,05) between groups in the number of macrophages. The results of the LSD test showed that there was a significant difference (p<0,05) between the treatment group and the positive and negative controls. Based on this research, 5% binahong leaf extract gel has an effect on the number of macrophages cells in the wound healing process after tooth extraction.